Discrete Optimization of Transmission Ratio of Two-speed AMT for Electric Vehicle - Zhu Yongqi; Huang Kang (Jixie chuandong)
The transmission ratios optimized by traditional optimization method often have a difference from the actual values decided by gear teeth matching. Based on a battery electric vehicle whose vehicle parameters and dynamics performance requirements are given,the parameters matching of driving motor is conducted firstly. Then,taking the numbers of teeth of transmission as variables,a discrete optimization method of transmission ratios is established,considering the New European Driving Cycle（NEDC） and the economic shift schedule. The results show that the optimal solution of the transmission ratios obtained from proposed method can make the motor driving system working in the high-efficiency area,and the ratios can be actually obtained by the gear teeth matching of transmission.